Protecting women, protecting the state: Militarism, security threats, and government action on violence against women in Jordan. (December 2019) - Forester, Summer
Contrary to our understanding of when states act on women's rights, Jordan adopted a policy on violence against women at the same time as it faced a number of external and internal security threats. In this article, I query the relationship between militarism and the gender policymaking process in Jordan to make sense of this puzzle. I specifically consider the ways in which a feminist conceptualization of militarism offers a more fruitful understanding of government action on violence against women in Jordan than studying this policy development through the lens of patriarchy, state institutions, and/or feminist activism alone. Indeed, evaluating the development of Jordan's Family Protection Law through the lens of militarism and related security practices reveals the depth and breadth of these phenomena: the martial values and priorities of the Jordanian regime extend beyond the realm of traditional, 'high politics' security issues and impact civil, social, and even interpersonal relations – relations that are always already gendered – that are seemingly far removed from military concerns. I argue that the Jordanian government adopted its policy on violence against women because this enhanced the state's image in the international arena and appeased domestic audiences by adhering to a gendered logic of protection that maintains the state as the ultimate protector of women. Overall, the article deepens our understanding of how militarism and the security climate influence the gender policymaking process, particularly in semi-authoritarian regimes.